Gaya Bahasa iltifât Dalam Al-Qurân: Kajian Struktur dan Makna - Mardjoko Idris (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Ilmu Tarbiyah Muhammadiyah Tempurrejo Ngawi, 2019)
Abstract Iltifât language is the Qur'an i'jâz, the structure that builds the style of this iltifat is very different from the buildings of the Arabic structure that we commonly know. The Iltifat style does not necessarily follow the rules of NAHWU or shoraf that are commonly adhered to. Therefore, to understand the style of the iltifat is in need of understanding the context that becomes the backdrop of a speech. Through the study of the Ltifat style in the Koran can be suggested that iltfat in the Koran sometimes happens to the form (Shiyagh), Numbers (' Adad), Dhamir (Dhamâir), Tools (Adawât), meaning (Mu'jam), and building Nahwu (al-Binâu An-Nahwy). Keywords: Iltifât, context, language style